Mycobacterium avium Subsp. avium and Salmonella enterica serotype Typhimurium var. Copenhagen phage type DT2 in pigeons - Kriz, Petr; Sisak, Frantisek; Slana, Iva; Karpiskova, Renata; Docekal, Jan; Skoric, Misa; Fictum, Petr; Babak, Vladimir; Pavlik, Ivo (Foodborne pathogens and disease, 2011)
We report on a coinfection of Mycobacterium avium subsp. avium and Salmonella enterica serotype Typhimurium var. Copenhagen phage type DT2 in pigeons from one flock, from which squabs were occasionally consumed by humans. Triplex quantitative real-time PCR and culture methods were used for M. a. avium detection in livers and culture method was used for the detection of Salmonella sp. in samples of liver and caecum of 33 examined birds. M. a. avium was detected in a total of 31 (93.9%) and Salmonella Typhimurium in a total of 11 (33.3%) pigeons. Coinfection with both pathogens was found in 10 (30.3%), infection with Salmonella Typhimurium alone in 1 (3.0%), and infection with M. a. avium alone in 21 (63.7%) pigeons. Neither pathogen was detected in one pigeon. There was no difference in clinical symptoms exhibited by pigeons infected by M. a. avium and/or Salmonella Typhimurium. All Salmonella Typhimurium isolates were sensitive to all 15 antimicrobials tested. According to these results we emphasize good heat treatment of consumed squabs.
Keywords: Bacteriophage Typing; Liver; játra; Real-Time Polymerase Chain Reaction; antiinfekční látky; Animal Husbandry; cékum; Česká republika; Tuberculosis, Avian; Anti-Infective Agents; Disease Outbreaks; Salmonella Infections, Animal; sérotypizace; Bird Diseases; Microbial Sensitivity Tests; Czech Republic; kvantitativní polymerázová řetězová reakce; chov zvířat; epidemický výskyt choroby; nemoci ptáků; zvířata; Humans; Salmonella typhimurium; Columbidae; koinfekce; Serotyping; fagotypizace; Mycobacterium avium; Coinfection; mikrobiální testy citlivosti; Cecum; ptačí tuberkulóza; salmonelová infekce u zvířat; lidé; Animals